Exploring the prevalence of severe obesity in a large teaching hospital - Ephrahim E. Jerry; Miriam A. Scheurwater; Janine J.P. Ghielen; Ilse van Donkelaar; Dennis van Veghel; Lukas R.C. Dekker; Simon W. Nienhuijs (PLoS ONE, 2025)
Background Obesity remains a critical public health issue in the Netherlands, where 50.2% of the population has a body mass index (BMI) over 25 kg/m2, 15.6% exceeds 30 kg/m2, and 3.5% meets the criteria for severe obesity (BMI ≥ 35 kg/m2). This study aimed to describe the prevalence and distribution of severe obesity across medical specialties in a large Dutch teaching hospital, to assess whether certain departments carry a disproportionate burden compared to national averages. Methods A retrospective cohort study was conducted at Catharina Hospital in Eindhoven, using patient data from 2022 and 2023. Patients with a history or current treatment for Metabolic Bariatric Surgery (MBS) were excluded. The highest registered BMI during the study period was used for analysis. Data was analyzed across specialties with attention to procedural volume and hospital burden. Additionally, all surgical procedures were reviewed in patients with BMI ≥ 35 kg/m2. Results In total, in 8.0% of all hospital visits patients had a BMI ≥ 35 kg/m2, compared to 3.5% in the general population. Specialties such as pulmonology (12.8%), internal medicine (10.4%), and orthopedic surgery (9.8%) showed a notably higher prevalence. Furthermore, a total of 5,472 surgical procedures were performed on patients with severe obesity, representing 13.5% of all surgical procedures. Common procedures included percutaneous coronary intervention in cardiology, laparoscopic cholecystectomy in general surgery, coronary artery bypass graft in cardiothoracic surgery, and total knee arthroplasty in orthopedic surgery. Conclusion Approximately one in thirteen hospital patients presents with severe obesity, and undergoes over 2,700 procedures annually, reflecting the scale at which severe obesity intersects with hospital-based healthcare. These findings emphasize the need for heightened awareness of obesity-related healthcare demands and the need for further research into the impact of severe obesity on surgical outcomes and use of hospital resources.